Development of a fast and efficient method to analyze microplastics in planktonic samples. (July 2021) - López-Rosales, Adrián; Andrade, Jose M.; Grueiro-Noche, Gloria; Fernández-González, Verónica; López-Mahía, Purificación; Muniategui-Lorenzo, Soledad
Abstract: Microplastics (MPs) affect plankton (a basis of the trophic chain) and planktivorous fish can ingest them through food confusion or by trophic transmission. Consensus to determine MPs in plankton is lacking and, so, three digestion treatments were evaluated: Alkaline (potassium hydroxide) and enzymatic (protease plus lipase) digestions, both combined with a hydrogen peroxide stage; and an oxidative method using a surfactant (sodium dodecyl sulfate) plus hydrogen peroxide. The alkaline method using potassium hydroxide was found to damage polystyrene. MPs were identified with a stereomicroscope and characterized by reflectance infrared microscopy in semi-automatic mode (using dedicated multi-well aluminium plates). Analytical recoveries for polypropylene, polystyrene, polyethylene, polyamide, polyvinyl chloride and polyethylene terephthalate were higher than 75%, 82% and 83% for the alkaline, enzymatic and oxidative treatments, respectively. The enzymatic method was successfully validated in a European interlaboratory exercise and the oxidative method was demonstrated to be a reliable, fast and cheaper alternative. Graphical abstract: Unlabelled Image Highlights: A cost-efficient, plastic-safe protocol was developed to digest plankton samples. Combining alkaline and oxidative treatments can be harmful in polystyrene MPs. Multi-well plates reduced the measurement time in a FTIR microscope. The enzymatic method was validated in a European interlaboratory exercise. The oxidative method is a reliable (and cheaper) alternative to the enzymatic one.